Economic Voting in Direct Democracy: A Case Study of the 2016 Italian Constitutional Referendum - Leininger, Arndt (2019)
Referendums provide citizens with more control over policy. At the same time, they often entail choices over highly complex policies and are politicised along partisan lines, suggesting that partisan rather than policy considerations will guide voters’ choices. I look to the 2016 Italian constitutional referendum, which was particularly complex and polarised, as an opportunity to test for mechanisms of government accountability in a referendum. Using a national survey of voters, I show that the more negative a respondent’s evaluation of the state of the economy, the lower their likelihood to vote ‘yes’ on the government’s reform proposal. This relationship is remarkably strong: an average respondent with a very positive evaluation of the state of the economy has an 88% probability of supporting the government’s reform proposal compared to only 12% for a respondent with a very negative evaluation. The fact that economic evaluations are a strong determinant of vote choice provides evidence for the existence of an economic vote in a referendum. This further suggests that voters may treat referendums as a sort of second-order election.